2021
DOI: 10.1177/02676591211019319
|View full text |Cite
|
Sign up to set email alerts
|

Optimising risk factors for atrial fibrillation post-cardiac surgery

Abstract: Postoperative atrial fibrillation (POAF) is an ongoing complication following cardiac surgery, with an incidence of 15%–60%. It is associated with substantial mortality and morbidity, as well increased hospital stays and healthcare costs. The pathogenesis is not fully understood, but the literature suggests that POAF occurs when transient, postoperative triggers act on vulnerable atrial tissue produced by preoperative, procedure-induced and postoperative processes such as inflammation, oxidative stress, autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
(321 reference statements)
1
4
1
Order By: Relevance
“…It was found that AF was mainly detected in the first three days after the surgery, with most patients being diagnosed on the second day. The same results were reported by Gjerakaroska et al (Gjerakaroska-Radovikj et al, 2020) and Goulden et al (Goulden et al, 2022). Associated factors such as autonomic imbalance before surgery, increase in catecholamines, pericardial inflammation, and changes in volume and pressure due to fluid shift contribute to POAF (Chang et al, 2019;Douketis et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…It was found that AF was mainly detected in the first three days after the surgery, with most patients being diagnosed on the second day. The same results were reported by Gjerakaroska et al (Gjerakaroska-Radovikj et al, 2020) and Goulden et al (Goulden et al, 2022). Associated factors such as autonomic imbalance before surgery, increase in catecholamines, pericardial inflammation, and changes in volume and pressure due to fluid shift contribute to POAF (Chang et al, 2019;Douketis et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
“…Understandably, the longer the operation, the more severe the risk factors such as ischemic injury or inflammation experienced by the patient ( 41 ). Notably, we did not find that the duration of cardiopulmonary bypass time and aortic cross-clamp time was significantly correlated with PAOF, which is varied in some previous studies ( 45 , 46 ). Therefore, apart from the duration of cardiopulmonary bypass and aortic cross-clamp, the effects and underlying mechanisms of other possible factors in the duration of surgery on POAF, such as the use of anesthetics, deserve further study in the future.…”
Section: Discussioncontrasting
confidence: 79%
“…Furthermore, the AUC of the resting heart rate is slightly greater than that for age, which is a well-established risk factor for POAF. [14][15][16] To the best of our knowledge, this is the first study to capture the value of the resting heart rate for predicting POAF in CTEPH patients who underwent PTE.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age has consistently been found to be an independent predictor of POAF, and the incidence of POAF among patients aged 72 or older is fivefold higher than that of patients aged 55 and younger. 16 Studies showed that age-related atrial myocardium remodeling played an important role in the development of AF. 26,27 CTEPH patients who underwent PTE tend to be younger than other cardiac surgery patients, the mean age of the patients in this study was only 51 ± 13 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation